Prediction of Ligands Binding Acetylcholinesterase with Potential Antidotal Activity: A Virtual Screening Approach. Issue 6 (4th April 2019) - Ochoa, Rodrigo; Rodriguez, Carlos A.; Zuluaga, Andres F.
Abstract: Intoxications caused by organophosphorus compounds (OPs) are associated with the reversible, and sometimes irreversible interaction with acetylcholinesterase (AChE). OPs are commonly used as pesticides mainly in developing countries, where the associated poisoning is a major health problem related to suicidal attempts, careless manipulation, and chemical warfare. The current antidotes are oxime‐based drugs that can regenerate the AChE catalytic activity. Nevertheless, challenges associated with lack of efficiency and difficulties for crossing blood‐brain barrier have motivated the design of novel alternatives. We used a validated molecular docking approach for the virtual screening of 579, 890 synthetic ligands and 478 drugs against a human AChE in its apo conformation, and a murine AChE conjugated with the OP tabun. After filtering, 7 hits were selected as potential competitors due to the formation of key interactions within the active site gorge of the AChE structure, and potential reactivators based on interactions with amino acids of the catalytic triad in the presence of organophosphorus compounds. The selected candidates will be further evaluated through in vitro and in vivo assays. Abstract :